Pharmacists as Stewards in Diabetes Mellitus: Current and Future Roles in Pakistan - Khan*, Majid (Journal of Pharmacy Practice and Community Medicine, 2026)
The global prevalence of diabetes mellitus is escalating daily (Khan, 2024; Khan et al., 2025). In Pakistan, the high costs of therapy and diagnosis approximately 11,580 PKR annually and 965 PKR/month, with 46% of these costs attributed to medications and 32% to laboratory investigations consume about 18% of a family’s income (Nasiri et al., 2019). Coupled with the complications of diabetes mellitus and oxidative stress (Naz et al., 2024) and in-turn significant noncompliance rates (Khan, 2022), these factors necessitate recognizing pharmacists as key stewards in diabetes management.
Keywords: Letter to Editor